2014
DOI: 10.1172/jci69778
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte-associated talin1 is critical for glomerular filtration barrier maintenance

Abstract: Podocytes are specialized actin-rich epithelial cells that line the kidney glomerular filtration barrier. The interface between the podocyte and the glomerular basement membrane requires integrins, and defects in either α 3 or β 1 integrin, or the α 3 β 1 ligand laminin result in nephrotic syndrome in murine models. The large cytoskeletal protein talin1 is not only pivotal for integrin activation, but also directly links integrins to the actin cytoskeleton. Here, we found that mice lacking talin1 specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
179
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(188 citation statements)
references
References 69 publications
(78 reference statements)
5
179
0
Order By: Relevance
“…The medical relevance of podocyte adhesion is underlined by the fact that podocyte detachment is a key factor for chronic kidney disease progression (32)(33)(34). Previous studies mainly focused on key components of the integrin adhesome, such as different integrin subunits or central signaling proteins such as ILK and TALIN (11,12,15). Despite those previous advances, there is still only limited knowledge about cell type-specific modulation of cell adhesion and contractility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The medical relevance of podocyte adhesion is underlined by the fact that podocyte detachment is a key factor for chronic kidney disease progression (32)(33)(34). Previous studies mainly focused on key components of the integrin adhesome, such as different integrin subunits or central signaling proteins such as ILK and TALIN (11,12,15). Despite those previous advances, there is still only limited knowledge about cell type-specific modulation of cell adhesion and contractility.…”
Section: Discussionmentioning
confidence: 99%
“…S5, S6, and S20). More recently, it was demonstrated that loss of TALIN (genetic deletion and experimental stress models), a well-established core focal adhesome component, results in a dramatic podocyte phenotype characterized by massive proteinuria, as well as consecutive development of glomerular sclerosis (15). Interestingly, TALINdeficient podocytes exhibited a mild adhesion and spreading defect, but a predominant misconfiguration of the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in these signaling pathways, frequently caused by genetic mutations within these networks that are responsible for biochemical dysfunctions in proteins and in their related signaling cascades, may progress to glomerular diseases (Wiggins, 2007;Mathieson, 2008). One of the key components of the podocyte signaling hub is nephrin, which appears to be controlled at multiple levels by the modulation of its phosphorylation state via Src family tyrosine kinases (Fyn, Yes, Src) and trafficking (Quack et al, 2006) or by a direct degradation process mediated by calpain (Peltier et al, 2006;Tian et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…39 Glomeruli were harvested and enriched from mice kidney cortical tissue with 45% Percoll solution (GE Healthcare BioSciences, Uppsala, Sweden) as previously described. 40 The kidneys were harvested immediately and washed in ice-cold Krebs-Henseleit saline solution (119 mM NaCl, 4.7 mM KCl, 1.9 mM CaCl 2 , 1.2 mM L KH 2 PO 4 , 1.2 mM MgSO 4 , 7H 2 O, and 25 mM NaHCO 3 , pH, 7.4). The renal cortex segments were dissected away and finely minced into small pieces, then incubated with 1 mg/ml collagenase (Roche, Mannheim, Germany) at 37°C for 30 minutes.…”
Section: Cell Culturementioning
confidence: 99%